Common identity of grapevine viroids from USA and Australia revealed by PCR analysis - Rezaian, M A; Krake, L R; Golino, D A (Intervirology, 1992)
Pairs of viroid-specific oligonucleotide primers were selected and used in separate reverse transcription reactions coupled with the polymerase chain reaction to obtain DNA products of predetermined sizes characteristic of each viroid. The reaction conditions allowed efficient incorporation of small amounts of 32P-dATP which enabled rapid detection of the products in polyacrylamide gels. Using this method as well as probe hybridization, the presence of grapevine yellow speckle viroids 1 and 2 (previously known as GV1B) in grapevine samples from California was demonstrated, and it was established that the Australian grapevine viroid occurs in California. These comparisons provide the basis for uniform nomenclature of grapevine viroids found in different geographical regions.